2021
DOI: 10.3389/fgene.2021.699141
|View full text |Cite
|
Sign up to set email alerts
|

A Codon-Pair Bias Associated With Network Interactions in Influenza A, B, and C Genomes

Abstract: A new codon-pair bias present in the genomes of different types of influenza virus is described. Codons with fewer network interactions are more frequency paired together than other codon-pairs in influenza A, B, and C genomes. A shared feature among three different influenza types suggests an evolutionary bias. Codon-pair preference can affect both speed of protein translation and RNA structure. This newly identified bias may provide insight into drivers of virus evolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…CPB has been summarized for bacteria, archaea, and eukaryotes [47] , [81] . For viruses, CPB was first described in poliovirus [45] , followed by classical swine fever virus [83] , human immunodeficiency virus type 1 [84] , [85] , porcine reproductive and respiratory syndrome virus [86] , dengue virus type 2 [87] , influenza A/Puerto Rico/8/34 (H1N1) virus [88] , Marek's disease herpesvirus [89] , [90] , Zika virus [91] , influenza A virus (IAV) [92] , influenza B virus [92] , and influenza C virus [92] . However, there have been no reports on CPB in plant viruses until now.…”
Section: Nucleotide Composition Of Plant Rna Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…CPB has been summarized for bacteria, archaea, and eukaryotes [47] , [81] . For viruses, CPB was first described in poliovirus [45] , followed by classical swine fever virus [83] , human immunodeficiency virus type 1 [84] , [85] , porcine reproductive and respiratory syndrome virus [86] , dengue virus type 2 [87] , influenza A/Puerto Rico/8/34 (H1N1) virus [88] , Marek's disease herpesvirus [89] , [90] , Zika virus [91] , influenza A virus (IAV) [92] , influenza B virus [92] , and influenza C virus [92] . However, there have been no reports on CPB in plant viruses until now.…”
Section: Nucleotide Composition Of Plant Rna Virusesmentioning
confidence: 99%
“…How about other dinucleotide frequency affect host adaptation and replication of plant RNA viruses. (vi) Codon pair bias has significant affect on the evolution of animal and human viruses [45] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] , however, there have been no reports on codon pair bias in plant RNA viruses. (vii) The CUB and dinucleotide bias is also related to amino acid conservation, gene length, protein structure and hydrophobicity level [32] , [135] , new methods of analyzing CUB and dinucleotide bias are required.…”
Section: Outstanding Questionsmentioning
confidence: 99%
“…If the first two nucleotides are guanosine (G) or cytosine (C) the network interactions are ‘strong’, and if the nucleotides are a combination then the network interactions are ‘intermediate’. Using this framework, we previously observed that codon pairs characterized by codons with weak network interactions were more frequently observed in influenza virus genomes 12 .…”
Section: Introductionmentioning
confidence: 99%